EVALUATION OF LAPAROSCOPIC CHOLECYSTECTOMY DIFFICULTY DURING THE COVID-19 PANDEMIC USING EXTERNALLY VALIDATED PREDICTION MODELS: A RETROSPECTIVE COHORT STUDY. - Panda, Kedarnath; Bhoi, Suraj Kumar; Saxena, Anuj (Student's Journal of Health Research Africa, 2024)
Background The COVID-19 pandemic has posed significant challenges to surgical procedures, including laparoscopic cholecystectomy (LC). Assessing the difficulty of these surgeries during the pandemic is crucial for optimizing outcomes and resource allocation. This study aims to evaluate the difficulty of LC during the COVID-19 pandemic using externally validated prediction models. Methods A total of 120 individuals who undertook LC or open cholecystectomy were included. The CholeS and Randhawa scoring systems were used to predict operative difficulty. Data on demographics, clinical presentation, laboratory results, and surgical outcomes were collected and studied using SPSS version 21.0. Results The mean age was 45.3 years, with 48.3% male and 51.7% female participants. The mean CholeS score was 8.5, and the mean Randhawa score was 7.1. Operative difficulty was classified as easy (33.3%), difficult (54.2%), and very difficult (12.5%). Significant correlations were found between higher preoperative scores and increased operative difficulty, longer operation duration, and higher complication rates. Specifically, the odds ratios for CholeS and Randhawa scores predicting operative difficulty were 1.25 (95% CI: 1.12-1.39) and 1.30 (95% CI: 1.15-1.45), respectively. Additional significant correlations were found with older age (OR 1.05, 95% CI 1.01-1.10), presence of diabetes mellitus (OR 2.75, 95% CI 1.15-6.58), higher ASA classification (OR 1.58, 95% CI 1.08-2.31), and longer hospital stay (OR 1.40, 95% CI 1.20-1.62). Conclusion Externally validated prediction models effectively assess the problems of LC during the COVID-19 pandemic. Higher preoperative scores were associated with increased operative challenges and complications. Recommendations Preoperative risk stratification using the CholeS and Randhawa scores should be integrated into clinical practice to improve surgical planning and patient outcomes.